Stellaris : people of the stars - Johnson, Les (Charles Les); Hampson, Robert E. (Baen, 2020)
Inspired by a gathering of scientists, science fiction authors, and futurists at a series of annual meetings held by the Tennessee Valley Interstellar Workshop, here are original science fiction stories and accessible speculative pieces by top scientists that will take you to that future! Enjoy stories from award-winning authors such as Kevin J. Anderson, William Ledbetter, Todd McCaffrey, and Sarah A. Hoyt, plus essays on the science behind the fiction from Martin Rees, Astronomer Royal of the United Kingdom, Mark Shelhamer, Chief Scientist for NASA's Human Research Program, and more! -- barnesandnoble.com